ANALISIS RAGAM PLATFORM E-LEARNING DALAM PEMBELAJARAN BIOLOGI KELAS XI SMA DAN MA NEGERI DI KOTA SEMARANG - Zahro', Anisatuz; Khoiri, Nur; Wijayanti, Erna (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
The emergence of Coronavirus-19 disease has caused all educational institutions to switch the face-to-face learning mode to distance learning with an online system. Online learning requires teachers and students to use a tool to help teaching and learning activities, namely the e-learning platform. The purpose of this study is to analyze the various e-learning platforms used by biology teachers in grade 11 of public senior high schools (SMA) and Islamic public high schools (MA) in Semarang City. This research is a qualitative descriptive study using the analysis of the Miles and Huberman model. The purposive sampling technique was used by considering the geographical location of the school and the diversity of platforms used. The samples were 5 schools: 3 high schools (SMA) and 2 Islamic Public high School of Madrasah Aliyah. Data collection techniques used semi-structured interviews and documentation studies. The results show that the e-learning platforms used by biology teachers are very diverse, ranging from instant messaging platforms such as WhatsApp, video conferencing platforms such as Google Meet and Microsoft Team, and Learning Management System (LMS) platforms such as Moodle, Google Classroom, Microsoft Office 365, and Madrasah e-learning. Each school uses a different type of platform and is adapted to school policies and student needs. Some schools develop their own e-learning platforms for online learning so that their use is mandatory, but this does not limit teachers from integrating other platforms so that learning objectives can be achieved perfectly.